Deconstructing difference: the rhetoric of human resource managers' diversity discourses - Zanoni, Patrizia; Janssens, Maddy (2004)
This article analyses texts on diversity produced in 25 interviews with Flemish human resource (HR) managers from a critical discourse analysis and rhetorical perspective. Following critical discourse analysis, we analyse how HR managers define diversity, how their diversity discourses reflect existing managerial practices and underlying power relations, and how they reaffirm or challenge those managerial practices and power relations. Specifically, we examine how power enters HR managers' local discourses of diversity through the very micro-dynamics of language by analysing the rhetorical schemes they use and the grand Discourses they draw from. This critical, text-focused approach to diversity discourses contributes to the development of a non-essentialist reconceptualization of diversity that acknowledges power. - Reproduced.
Keywords: Human resources development